2019
DOI: 10.3390/cells8101257
|View full text |Cite
|
Sign up to set email alerts
|

Where to Stand with Stromal Cells and Chronic Synovitis in Rheumatoid Arthritis?

Abstract: The synovium exercises its main function in joint homeostasis through the secretion of factors (such as lubricin and hyaluronic acid) that are critical for the joint lubrication and function. The main synovium cell components are fibroblast-like synoviocytes, mesenchymal stromal/stem cells and macrophage-like synovial cells. In the synovium, cells of mesenchymal origin modulate local inflammation and fibrosis, and interact with different fibroblast subtypes and with resident macrophages. In pathologic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Hyaluronic acid (HA), a negatively charged, nonsulfated glycosaminoglycan ubiquitous both in synovial fluid and articular cartilage [ 24 , 25 ], was for many years, assumed to be the molecule responsible for cartilage lubrication [ 26 , 27 ]. Clearly, HA plays a major role in joint homeostasis [ 28 , 29 , 30 ]; however, its boundary lubricating ability is poor, as directly determined experimentally by surface force balance (SFB) investigations [ 31 , 32 , 33 ]. Recent studies by Seror et al [ 33 ] and Zhu et al [ 34 ] demonstrated that the friction between two surface-attached HA layers was much reduced (from μ ≈ 0.3 to μ ≈ 0.001) after adding small unilamellar vesicles (SUVs) composed of PC lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid (HA), a negatively charged, nonsulfated glycosaminoglycan ubiquitous both in synovial fluid and articular cartilage [ 24 , 25 ], was for many years, assumed to be the molecule responsible for cartilage lubrication [ 26 , 27 ]. Clearly, HA plays a major role in joint homeostasis [ 28 , 29 , 30 ]; however, its boundary lubricating ability is poor, as directly determined experimentally by surface force balance (SFB) investigations [ 31 , 32 , 33 ]. Recent studies by Seror et al [ 33 ] and Zhu et al [ 34 ] demonstrated that the friction between two surface-attached HA layers was much reduced (from μ ≈ 0.3 to μ ≈ 0.001) after adding small unilamellar vesicles (SUVs) composed of PC lipids.…”
Section: Introductionmentioning
confidence: 99%
“…RRV infection has been shown to promote glycolytic pathways in vitro , however a clear relationship between glycolytic pathways and IL-17 signaling in arthritic disease remains to be established [ 93 ]. In addition, studies have shown that differentiation and proliferation of IL-17–producing Th17 cells from naïve CD4 + T cells requires significant cellular metabolic changes, and these changes are essential in nutrient-poor environments such as the acidic environment found in inflamed RA joints [ 94 , 95 ]. Among genes upregulated in CD45 + cells from IL-17A/F mAb-treated mice, SLC27A1 encodes FATP1 (fatty acid transport protein-1), which helps control lipid and glucose metabolism, and has been associated with anti-inflammatory phenotypes in macrophages by acting as a modulator of oxidative stress [ 96 ], and is highly expressed in skeletal tissues during steady-state [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to several autoimmune diseases such as RA, epigenetic modifications have also been shown to increase inflammation in tissues through pro-inflammatory transcription factor nuclear factor kappa B (NF-κB) activation [ 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 ]. Furthermore, the epigenetic phenomena underlying the anti-inflammatory potential of diet and lifestyle conditions have resulted in the development of therapeutic actions to alleviate constant inflammation affecting the epigenome.…”
Section: Treatment Strategies In Ramentioning
confidence: 99%